Detection of Mycoplasma hyopneumoniae in Bronchoalveolar Lavage Fluids of Pigs by PCR - Baumeister, A. Katrin (American Society for Microbiology, 1998)
In the present investigation we developed a method for the detection of Mycoplasma hyopneumoniae in bronchoalveolar lavage fluid (BALF) of pigs by PCR with a primer pair flanking a DNA fragment of 853 bp specific for M. hyopneumoniae. Several methods were tested to eliminate the amplification inhibitors present in BALFs. The best results were obtained by the extraction of the DNA from the BALFs. By the PCR performed with the extracted DNA, 10(2) CFU of M. hyopneumoniae could be detected in 1 ml of BALF from specific-pathogen-free swine experimentally inoculated with M. hyopneumoniae. DNA from 11 other mycoplasma species and 17 cell-walled bacterial species colonizing the respiratory tracts of pigs was not amplified. In a field study BALFs from 40 pigs from farms with a history of chronic pneumonia were tested for M. hyopneumoniae by cultivation and by PCR (i) with BALFs incubated in Friis medium and (ii) with DNA extracted from the BALFs. In addition, PCR was performed with postmortem lung washings from 19 of the 40 pigs, and immunofluorescence tests were carried out with sections of lungs from 18 of the 40 pigs. M. hyopneumoniae could not be detected in 18 of the 40 pigs by any of the five methods tested. The remaining 22 pigs showed a positive reaction by the PCR with DNA extracted from the BALFs and variable positive reactions by the other tests. A complete correspondence could be observed between the immunofluorescence test result and the result of PCR with DNA. The investigation shows that the PCR with DNA extracted from BALFs is a suitable technique for the sensitive and specific in vivo detection of M. hyopneumoniae.